Estimated Prevalence and Demographic Correlates of Compulsive Sexual Behavior Among Gay Men in the United States. Issue 9 (12th August 2021) - Gleason, Neil; Finotelli, Itor; Miner, Michael H.; Herbenick, Debra; Coleman, Eli
ABSTRACT: Background: Compulsive sexual behavior (CSB) is a clinical syndrome that causes significant distress and impairment for many individuals in the United States. Gay men are thought to have a higher prevalence of CSB, and it is associated with many relevant health outcomes including HIV risk behavior. Aim: To estimate the prevalence and examine demographic correlates of CSB among gay men in the United States. Methods: A U.S. national probability sample of 227 gay-identified men were collected as part of the 2015 National Survey of Sexual Health and Behavior (NSSHB). Outcomes: Participants completed the Compulsive Sexual Behavior Inventory (CSBI-13) and demographic measures. RESULTS: Eighteen participants (7.93%) scored above the CSBI-13 clinical cut point, indicating they would likely meet criteria for clinically significant compulsive sexual behavior. To assess demographic correlates of CSB, demographic variables were entered into a logistic regression. Results of the logistic regression indicated that participant age, education, and religious affiliation were significant predictors of CSB status. Individuals scoring above the cut point were younger on average ( M = 39.17; SD = 14.84) than those scoring below the cut point ( M = 47.52; SD = 14.62; P = .02). Odds of scoring above the cut point were about six times greater for religiously affiliated participants compared to non-religiously affiliated participants ( P = .005), and four times greater for those who had attended college compared to those who had not ( P = .03). Clinical Implications: These results indicate the prevalence of CSB in gay men is more modest than previously estimated, and is similar to the general population prevalence estimated in a previous study. The strongest predictor of CSB in this sample was religious affiliation, which underscores the importance of evaluating the role of religiosity in the etiology and/or identification of this clinical syndrome. Strengths and Limitations: These findings are strengthened by the national probability sampling methodology and the use of the empirically validated CSBI-13 cut point. However, this sample was also older and had higher income and educational attainment than the larger population of gay men in the U.S. CONCLUSION: These results indicate gay men may have a CSB prevalence rate similar to the general population, which contradicts previous research suggesting they are at greater risk for CSB.